The Brief of Al-Tahtheeb in the Interpretation, by Imam Al-Mu’ayyad Bellah, Surat Al-Nisa from verse (174) to the end of it – Study and Investigation - Abbass, Farouq Ali Yahya Othman (Journal of Islamic Sciences, 2023)
The research aims to introduce the owner of the manuscript and his life، and to introduce the manuscript and to contribute to making the manuscript an easy، accessible and useful book that can be referenced with ease and ease. The research consists of: an introduction، two chapters، a conclusion، and indexes. The researcher used the descriptive analytical method، and the scientific method used in the investigation، and reached a number of results; The most important ones: 1- The author of the manuscript is Imam Al-Mu’ayyad Billah Muhammad bin Ismail bin Al-Imam Al-Qasim bin Muhammad، peace be upon them (died in the year: 1097 AH)، and the book “Al-Tahdheeb fi Tafsir” was shortened by Imam Al-Hakim Al-Jashmi; Limited in that to the descent، and the meaning، and provisions. 2- The manuscript contains a great deal of scholarly material not only in exegesis; Rather، it is a large scientific encyclopedia in which there are many sciences and arts، such as: the science of readings، doctrine، and jurisprudence. 3- The sources and references that studied the life of the imam show that he was a great scholar، and an imam of the imams of Yemen، just، merciful to the people، pious and a lot of fear of God Almighty. 4- Imam Al-Mu’ayyad Billah did not disclose the sources he referred to in his manuscript، but with the study and tracing of the manuscript، the sources from which he was taken became clear.